2015
DOI: 10.1121/1.4934958
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of interfacial stiffnesses of a tri-layer using Zero-Group Velocity Lamb modes

Abstract: Zero-Group Velocity (ZGV) Lamb waves are studied in a structure composed of two plates bonded by an adhesive layer. The dispersion curves are calculated for a Duralumin/epoxy/Duralumin sample, where the adhesion is modeled by a normal and a tangential spring at both interfaces. Several ZGV modes are identified and their frequency dependence on interfacial stiffnesses and on the bonding layer thickness is numerically studied. Then, experiments achieved with laser ultrasonic techniques are presented. Local reson… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…The experimental and theoretical ZGV frequencies are in reasonable agreement. The residual ~2 % mismatch may be caused either by a difference in the Si 3 N 4 layer parameters (see Supplementary Note 2) or to imperfect adhesion between the two layers 12,13 . The two other ZGV Lamb modes, predicted near 3 and 7 GHz, could not be detected.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental and theoretical ZGV frequencies are in reasonable agreement. The residual ~2 % mismatch may be caused either by a difference in the Si 3 N 4 layer parameters (see Supplementary Note 2) or to imperfect adhesion between the two layers 12,13 . The two other ZGV Lamb modes, predicted near 3 and 7 GHz, could not be detected.…”
Section: Resultsmentioning
confidence: 99%
“…defect detection, and adhesion testing [20][21][22][23][24]. In the case of Lamb waves in plates, it was also demonstrated that mode conversion between backward-propagating and forwardpropagating waves (or vice versa) at a step change in thickness leads to negative refraction, a process in which the refracted ray leaves the interface at an angle that is on the opposite side of the interface normal to that predicted by the usual Snell's law [25,26].…”
Section: Published By the American Physical Society Under The Terms Omentioning
confidence: 99%
“…Due to the localized resonances, ZGV modes are ideal for localized measurements of material properties because the clamping of the material is not important if excitation and measurement are sufficiently far from the clamping boundaries. ZGV modes have been used for locally measuring the Young's modulus or thickness of single-or multi-layered materials [17], [20], [21]. ZGV modes can be generated by a impulse from a pulsed laser source and detected using a laser interferometer [20].…”
Section: Background Of Acoustic Measurementsmentioning
confidence: 99%
“…2 Therefore, we built up our own experimental setup. The setup we chose to use are commonly used by other researchers [17], [20], [21] to investigate ZGV Lamb waves.…”
Section: Simulation and Analysismentioning
confidence: 99%